Makna Prosesi Pelaksanaan Poseriwu dalam Upacara Kematian pada Masyarakat Etnik Muna - La Diysi . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This study aims to describe the implementation of ritual procession of poseriwu and to analyze the symbolic meaning of objects contained in poseriwu ritual procession on Muna ethnic community. This study uses descriptive qualitative data, in which researchers try to give an overview of the implementation of poseriwu procession and interpret the symbolic meaning of objects in poseriwu procession in Muna ethnic community. The results of this study show that: (1) The procession of poseriwu consists of two stages: kabubusino koburu (grave watering) and the reading of a prayer of the haroa turuntana held at the family home of someone who is being poseriwu; (2) The symbolic meaning in the implementation of poseriwu, especially the content of haroa turuntana is a traditional food of Muna ethnic community and is the completeness that must be provided in poseriwu procession in Muna ethnic tradition. The meaning of those simbolic things are the symbol of human’s body which is constructed as the order of human body shape Keywords: poseriwu, kabubusino koburu, haroa turuntana, traditional food, Muna ethnic community